Jeyakāntaṉ mutal Civacaṅkari varai : tiṟaṉāyvu nūl - Āṟumukam, Pūvai Es., 1925- (Maṇiyam Patippakam, 1983)
Criticism of ten contemporary Tamil novelists: Jeyakāntaṉ, b. 1934, Civacaṅkari, b. 1942, etc.